Moderasi Peluang Pertumbuhan Dan Pengaruhnya Pada Nilai Perusahaan Manufaktur Di Bursa Efek Indonesia - Uray, Andrey Indra Maulana; Ariffin, Muchammad; Hidayat, Nur; Gusti, Girang Permata (Jurnal Ekonomi STIEP, 2024)
This study intends to identify the factors that influence the value of manufacturing companies listed on the Indonesia Stock Exchange, including dividend policy, profitability, firm size, and capital structure tempered by growth potential. This study is a quantitative research project, and the financial statements of 48 manufacturing businesses listed on the IDX were the source of the data used in this study. In order to do moderated regression analysis (MRA), this data is used. Eviews is the analytical tool employed. The findings demonstrated that business value is positively and significantly influenced by capital structure, profitability, and firm size. The impact of dividend policy on business value is both favorable and negligible. Growth potential acts as a moderator, reducing the link between capital structure and business value.